Guidance note for peace-informed programming at the Green Climate Fund: Health, food, and water security - Scartozzi, Cesare M; Caroli, Giulia; Sarzana, Carolina; Läderach, Peter R.D.; Pacillo, Grazia; Hyslop, Daniel; Hahn, Andreas Luis; Azar, Elio; Nicatore, Giorgia; Brown, Oliver; Hassamal, Komal; Ehmsen, Simon (2023)
Conflict has a deep and interrelated impact on health, food, and water security. With agriculture heavily dependent on freshwater withdrawals, disruptions to water supplies can heavily affect food production, which in turn affects health. In fragile and conflict-affected settings, poor governance and climate change exacerbate these challenges, leading to heightened competition for resources and the weaponization of vital assets like water. Projects in such locations, if not aware of conflict dynamics, can inadvertently exacerbate grievances and undermine their contributions to peace and stability – two key factors needed for long-term success in climate adaptation. Hence, incorporating conflict-sensitivity is vital for effective programming in these settings.